Celestine Sibley, reporter - Sibley, Celestine (Hill Street Press, 2001)
This in-depth and chronological selection takes the best of the best from Celestine Sibley's days as a beat reporter: from her stint, beginning in 1932 at age fifteen, as a cub reporter at the Mobile Press, through her work with the Pensacola News-Journal, and the high points of her career at the Atlanta Journal-Constitution.